Disruption of the Bone Morphogenetic Protein Receptor 2 Pathway in Nitrofen‐Induced Congenital Diaphragmatic Hernia. (18th June 2013) - Gosemann, Jan‐Hendrik; Friedmacher, Florian; Fujiwara, Naho; Alvarez, Luis A. J.; Corcionivoschi, Nicolae; Puri, Prem
<x xml:space="preserve">Abstract</x> BACKGROUND/PURPOSE Congenital diaphragmatic hernia (CDH) remains a major therapeutic challenge despite advances in neonatal resuscitation and intensive care. The high mortality and morbidity in CDH has been attributed to pulmonary hypoplasia and persistent pulmonary hypertension (PH). Bone morphogenetic protein receptor 2 (BMPR2) plays a key role in pulmonary vasculogenesis during the late stages of fetal lung development. BMPR2 is essential for control of endothelial and smooth muscle cell proliferation. Dysfunction of BMPR2 and downstream signaling have been shown to disturb the crucial balance of proliferation of smooth muscle cells contributing to the pathogenesis of human and experimental PH. We designed this study to investigate the hypothesis that BMPR2 signaling is disrupted in nitrofen‐induced CDH. METHODS Pregnant rats were treated with nitrofen or vehicle on gestational day 9 (D9). Fetuses were sacrificed on D21 and divided into CDH and control. Quantitative real‐time polymerase chain reaction, Western blotting, and confocal‐immunofluorescence were performed to determine pulmonary gene expression levels and protein expression of BMPR2 and related proteins. RESULTS Pulmonary Bmpr2 gene expression levels were significantly decreased in nitrofen‐induced CDH compared to controls. Western blotting and confocal microscopy revealed decreased pulmonary BMPR2 protein expression and increased activation of p38MAPK in CDH compared to controls. CONCLUSION The observed disruption of the BMPR2 signaling pathway may lead to extensive vascular remodeling and contribute to PH in the nitrofen‐induced CDH model. BMPR2 may therefore represent a potential target for the treatment of PH in CDH.